Biomass analysis of catch date in Central Philippine waters for the period 1978-1987 - Avillanosa, Arlene L. (Miagao, Iloilo College of Fisheries and Ocean Sciences, University of the Philippines in the Visayas, 2005)
This study initiates significantly the application of a spatially and temporally integrated management tool for fishery stock assessment. Further, a "management blueprint" and technology for fish resources of Philippine internal archipelagic waters is made available. Initially, BFAR 10-year municipal and commercial catch data from Central Philippine waters that satisfied MCM requirements were negotiated from BAS. Secondly, modes of the data sets are decomposed separately using the model to remove inconsistencies. Thirdly, analysis proceeds to trace the presence of biomass fluxes in the study area. The model demonstrates that give only si\ufficient spatial and temporal catch data, indications of biomass movements, abundance, and stock composition can be obtained. Lastly, the study' attempt at assessing BFAR methodology concluded that non-trivial errors are possible because data sources appear dubious and likely aggravated by inadequate funds. Several funds have significant implications to Philippine fisheries: 1)assessment of data errors ; 2)Implications of the dynamics f biomass sources and sinks to traditional concepts of exploitation and sustainability ; and 3)Potential indication of the presence of biomass fluxes. Certainly, these results could improve with more data and more involved stakeholder's participation from all over the country. It does seem that sufficient resources are required for proper sampling, data processing, and appropriate analysis of data. The task is for the particular goverment agency to conduct timely surveys. Only trained personnel capable of scientific sampling are deemed as appropriate enumerators. Finally, recognizing weaknesses of existing tools, especially foreign ones, the MCM technology is recommended as an effective alternative tool for stock assessment in the Philippine archipelago.
Thesis - M.S. in Fisheries (Fisheries Biology) - Institute of Marine Fisheries and Oceanology, College of Fisheries, U.P. in the Visayas
Keywords: Biomass analysis